ANTI-CRISIS MANAGEMENT IN THE FIELD OF HOTEL AND RESTAURANT BUSINESS IN THE COVID-19 PANDEMIC CONDITIONS - Коробейникова, Ярослава; Побігун, Олена (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The tourism industry is susceptible to changes in socio-economic and natural-man-made nature, which requires unique approaches in the management of hospitality enterprises. The article substantiates the need to adapt to the new conditions of the pandemic and develop a clear policy in such a crisis. We determined that the tools of crisis management are the priority. Anti-crisis management during a pandemic should be flexible and efficient in decision-making. The state and dynamics of the hotel industry in Ukraine in recent years are analyzed. We determined that the demand for hotel services due to the pandemic is significantly reduced, and, consequently, the losses to the market are significant. We analyzed the hotel and restaurant business losses during the quarantine period in the Radisson Blu Resort Bukovel hotel example. We considered the hotel’s security measures for guests and employees during the Covid-19 pandemic. The necessity of systemic anti-crisis management measures in the field of hospitality after a long period of the Covid-19 pandemic, which consists of the development of various scenario anti-crisis solutions, is substantiated. The necessity of monitoring the situation in combination with the teamwork of the hotel and restaurant enterprise specialists is substantiated. The proposed solutions algorithm will successfully overcome the pandemic crisis with minor losses for hotels and restaurants. Practical ways of realizing of stages of anti-crisis management for hotel and restaurant enterprises, such as working with the client and personnel and conducting product policy, are offered. We presented the system of measures in the structure of anti-crisis management, their main content, and the expected results of implementing these measures. We highlighted practical steps in optimizing costs and revenues, strengthening the digitalization of the industry, including working with clients, especially regular customers, and working with the institution’s staff. The development and implementation of integrated programs for guests in hotel and restaurant complexes are substantiated, which allows the performance of the modern tourist trend - tourism of impressions.